Fast Transport Pathways Into the Northern Hemisphere Upper Troposphere and Lower Stratosphere During Northern Summer. Issue 3 (8th February 2020) - Wu, Yutian; Orbe, Clara; Tilmes, Simone; Abalos, Marta; Wang, Xinyue
Abstract: This study identifies the fast (i.e., ∼ days–weeks) transport pathways that connect the Northern Hemisphere surface to the upper troposphere and lower stratosphere (UTLS) during northern summer by integrating a large (90 member) ensemble of Boundary Impulse Response tracers in the Whole Atmosphere Community Climate Model version 5. We show that there is a fast transport pathway that occurs over the southern slope of the Tibetan Plateau, northern India, the Arabian Sea, and Saudi Arabia; furthermore, we show that during July this pathway connects the Northern Hemisphere surface to the UTLS on a modal time scale of 5–10 days. A less efficient transport pathway is also identified over the western Pacific. A detailed budget analysis reveals that, while convective processes are responsible for transport to 200–300 hPa, the resolved dynamics, specifically the vertical eddy flux, dominate at 100–150 hPa. Transport variations are analyzed on weekly, monthly, and interannual time scales and are largely related to differences in the resolved dynamics in the UTLS. Key Points: A fast transport pathway into the UTLS is found over the southern slope of the Tibetan Plateau and northern India Resolved dynamics, specifically the vertical eddy flux, dominate transport into the UTLS Variability of northern summer tracer transport is analyzed with respect to weekly, monthly, and interannual time scales